Telomerase subunit Est2 marks internal sites that are prone to accumulate DNA damage - Satyaprakash Pandey (BMC, 2021)
Abstract Background The main function of telomerase is at the telomeres but under adverse conditions telomerase can bind to internal regions causing deleterious effects as observed in cancer cells. Results By mapping the global occupancy of the catalytic subunit of telomerase (Est2) in the budding yeast Saccharomyces cerevisiae, we reveal that it binds to multiple guanine-rich genomic loci, which we termed “non-telomeric binding sites” (NTBS). We characterize Est2 binding to NTBS. Contrary to telomeres, Est2 binds to NTBS in G1 and G2 phase independently of Est1 and Est3. The absence of Est1 and Est3 renders telomerase inactive at NTBS. However, upon global DNA damage, Est1 and Est3 join Est2 at NTBS and telomere addition can be observed indicating that Est2 occupancy marks NTBS regions as particular risks for genome stability. Conclusions Our results provide a novel model of telomerase regulation in the cell cycle using internal regions as “parking spots” of Est2 but marking them as hotspots for telomere addition.